PRESERVING CULTURAL IDENTITY AND INTERCULTURAL COMMUNICATION - Parmonova Mohigul Odiljon qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Maintaining cultural identity and intercultural dialogue are among the important themes in the modern world. At a time when globalization processes are gaining momentum, different peoples and nations are trying to preserve their cultures, maintain  their  own  unique  traditions  and  Customs.  At  the  same  time,  intercultural dialogue is an important tool in the development of mutual understanding, respect and cooperation  between  the  peoples  of  the  world.  And  finding  a  balance  between maintaining  cultural  identity  and  intercultural  dialogue  is  a  complex  but  necessary process.